2018
DOI: 10.1186/s12889-018-5513-7
|View full text |Cite
|
Sign up to set email alerts
|

“We don’t want our clothes to smell smoke”: changing malaria control practices and opportunities for integrated community-based management in Baringo, Kenya

Abstract: BackgroundThe decline in global malaria cases is attributed to intensified utilization of primary vector control interventions and artemisinin-based combination therapies (ACTs). These strategies are inadequate in many rural areas, thus adopting locally appropriate integrated malaria control strategies is imperative in these heterogeneous settings. This study aimed at investigating trends and local knowledge on malaria and to develop a framework for malaria control for communities in Baringo, Kenya.MethodsClin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…This finding is similar to previous quantitative studies where few methods were being integrated due to lack of knowledge [45][46][47]50]. Similar to our study, knowledge and use of LLINs was prominent in previous qualitative and quantitative studies including in Kenya and Tanzania [40,44,47,49]. Adequate knowledge on LLINs among populations may be attributed to the mass campaigns on use of mosquito nets including by the Ugandan Ministry of Health [8].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is similar to previous quantitative studies where few methods were being integrated due to lack of knowledge [45][46][47]50]. Similar to our study, knowledge and use of LLINs was prominent in previous qualitative and quantitative studies including in Kenya and Tanzania [40,44,47,49]. Adequate knowledge on LLINs among populations may be attributed to the mass campaigns on use of mosquito nets including by the Ugandan Ministry of Health [8].…”
Section: Discussionsupporting
confidence: 90%
“…Herbs that were used for malaria prophylaxis can easily be collected from gardens, bushes, as well as nearby shrubs and neighbourhoods [38]. Previous qualitative and quantitative studies in Uganda [38,39], Kenya [40][41][42], West Africa [43], Tanzania [44], and India [45] have all reported burning of cow dung and plant repellents to prevent mosquito bites and entry into houses. Eating herbal plants in groundnut paste to prevent malaria has also been documented elsewhere [38].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on oral HIV self-testing [22] and on self-collection of samples for cervical cancer screening [23] in the same geography of our study (Mombasa) reported users' high acceptability of these approaches, which reduced users' dependency on traditional testing conducted by HCWs. In fact, Kenya has a broad tradition of community-grounded strategies for conditions as varied as soil-transmitted helminths [24], malaria [25] or violence and discrimination against LGBT+ persons [26]. These strategies have in common a willingness to understand the communities' health needs and resources, and to empower both community members and cadres of healthcare practitioners other than nurses or physicians.…”
Section: Discussionmentioning
confidence: 99%
“…There is lack of strong and efficient collaboration between the Ministry of Health and Wellness malaria programme and other relevant government sectors/ministries, the private sector, the community/public and academia who are all essential in malaria control and elimination in Botswana [29]. Several studies suggest there is a positive impact of intersectoral collaboration in malaria control and elimination [21,[88][89][90][91][92][93]. Effective inter-sectoral collaboration is, however, influenced by factors such the approach, resources, relationships, management and shared vision [94].…”
Section: Intersectoral Collaborationmentioning
confidence: 99%